(untitled) - Elliott, Brian S. (New York, 2007)
This quick-find reference provides illustrations, descriptions, and relevant calculations for 2,000 time-tested electromechanical components which are essential to the design, repair, or operation of your electromechanical devices
Keywords: Electromechanical devices,Thiết bị cơ điện